Nitrite exposure on gills of Oreochromis niloticus: structure change, immune response, and apoptosis - Song, Chaowei; Zhu, Tiansheng; Cai, Ran; Yu, Yang; Liu, Ziyan; Yan, Jianing; Lian, Yingying; Li, Jiaqi; Li, Wensheng (Frontiers in Marine Science, 2025)
Nitrite is one of the most common pollutants in high-density aquaculture systems and has a potentially serious impact on the health of fish. The gill, as the organ directly in contact with the environment, performs several vital physiological functions, including gas exchange, osmotic pressure regulation, and mucosal immunity. Using a series of nitrite concentration gradients, we investigated the impact of nitrite on tilapia gills, with a focus on its immune responses. The results indicated that nitrite exposure could significantly increase the number of mucus cells and change the subtypes of chloride cells. Nitrite exposure significantly elevated serum catalase (CAT) activity and decreased superoxide dismutase (SOD) activity. After nitrite treatment, the expression of ion channel protein genes was markedly affected, with a substantial increase in Na+/Cl− cotransporter (ncc) expression. Inflammatory gene expression in the gill was also significantly altered. Both in vitro and in vivo experiments revealed that key genes in the IL-17 signaling pathway were considerably altered after nitrite exposure. Mitochondrial damage and apoptosis in the gill tissues were also found after nitrite exposure. In conclusion, nitrite exposure altered immune function and ion transport, especially the activation of the IL-17 signaling pathway, damage to mitochondrial structure, and apoptosis in the gill. This study enhances our understanding of the mechanisms underlying nitrite-induced damage to the gill.